Empowering Rapid Response To Heart Disease In Community Self-Help Efforts At Posyandu Kemuning 1a Sukamakmur Village Ciomas - Aminah Lily, Nyayu Siti; Wahyuni, Yuli; Saadah, Aas (Society : Jurnal Pengabdian Masyarakat, 2025)
The results of the 2022 Service Team questionnaire survey at Posyandu Kemuning 1A Sukamakmur Ciomas Village require regular heart checks, so far the midwife uses a stethoscope and the data is stored using a manual book so that it is inconvenient for patients to do pregnancy control per month. The main purpose of pregnancy checks is to keep the pregnancy healthy, monitor the growth and development of the fetus so that it is detected as early as possible abnormalities of the fetus and pregnant women, so it is necessary to transfer knowledge through socialization activities and mentoring of heart check health training. The outputs produced in this activity are the use of science and technology technology for the community including the use of heart medical records for checking heart disease and research results, optimizing community services, and helping to create peace and comfort in the community and helping to facilitate early heart checks. This activity also resulted in publications in community service journals, articles in several electronic publication media, activity videos, product IPR. This community service implements IKU 2, namely students gaining experience outside the campus and IKU 3 where lecturers carry out activities outside the campus and IKU 5, namely the work of lecturers is used by the community.